Development of a rapidly dispersing tablet of a poorly wettable compound—formulation DOE and mechanistic study of effect of formulation excipients on wetting of celecoxib - He, Xiaorong; Barone, Michael R.; Marsac, Patrick J.; Sperry, David C. (International journal of pharmaceutics, 2008)
Celecoxib has extremely poor aqueous wettability and dispersibility. A dispersibility method was developed to study the effects of formulation excipients and processing methods on wetting of celecoxib. In this method, a tablet or powder was placed in water and the turbidity of the resulting “dynamic” suspension was measured. Higher turbidity values reflect better dispersibility. Results show that wet granulation facilitates better drug dispersion than does dry granulation or direct compression. Results from a screening formulation statistical design of experiments (DOE) show that sodium lauryl sulfate (SLS), an anionic surfactant, gives higher celecoxib dispersibility than polysorbate 80, a neutral surfactant. Polyplasdone XL as a disintegrant results in better celecoxib dispersibility than sodium starch glycolate. The binder Kollidon 30 leads to better dispersibility, but slower disintegration than Kollidon 12. Jet-milling celecoxib with excipients not only improves dispersibility of the drug but also the ease of material handling. The method of microcrystalline cellulose addition does not significantly impact tablet properties. The effect of critical formulation variables on the wettability of celecoxib was further examined in prototype formulations. It is found that ionic surfactant resulted in better dispersibility than a neutral surfactant, probably due to charge dispersion. Kollidon 30 gives better drug dispersion than hydroxypropylmethyl cellulose and hydroxypropyl cellulose. This may be explained through a surface energy calculation, where the spreading coefficients between Kollidon 30 and celecoxib indicate formation of open porous granules in which pores can facilitate water uptake. The mode of disintegrant addition also impacts dispersibility of the drug. Dense granules were formed when the disintegrant, Polyplasdone, was added intra-granularly. As the extra-granular portion of the disintegrant increases, the dispersibility of the drug increases as well. The drug initial dispersibility (turbidity at 5 min during the dispersibility test) increases as the tablet porosity increases. A 3-factor face-centered experimental design was conducted to optimize the levels of surfactant (SLS), binder (Kollidon 30) and disintegrant (Polyplasdone). Within the range that was studied, the dispersibility of micronized drug increases as the amount of SLS and Kollidon 30 increases. The level of Polyplasdone has no significant impact on the dispersibility of micronized drug; however, higher levels of Polyplasdone lead to significantly harder tablets.